2013
DOI: 10.1210/en.2012-1421
|View full text |Cite
|
Sign up to set email alerts
|

Calorie-Restricted Weight Loss Reverses High-Fat Diet-Induced Ghrelin Resistance, Which Contributes to Rebound Weight Gain in a Ghrelin-Dependent Manner

Abstract: Twelve weeks of high-fat diet feeding causes ghrelin resistance in arcuate neuropeptide Y (NPY)/agouti-related protein (AgRP) neurons. In the current study, we investigated whether diet-induced weight loss could restore NPY/AgRP neuronal responsiveness to ghrelin and whether ghrelin mediates rebound weight gain after calorie-restricted (CR) weight loss. Diet-induced obese (DIO) mice were allocated to one of two dietary interventions until they reached the weight of age-matched lean controls. DIO mice received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 56 publications
7
57
0
4
Order By: Relevance
“…The extent of weight gain by the mice in our study is very similar to that in previous reports using a similar diet. Indeed, a 40% reduction in energy intake in obese mice rapidly reduces body weight and fat mass to that of control mice within 15 days [23]. Consistent with these observations we demonstrated that, in general, CR in HFD-induced obese mice reduced body weight by~7 g and fat mass by 4e5 g within 20 days.…”
Section: Discussionsupporting
confidence: 88%
“…The extent of weight gain by the mice in our study is very similar to that in previous reports using a similar diet. Indeed, a 40% reduction in energy intake in obese mice rapidly reduces body weight and fat mass to that of control mice within 15 days [23]. Consistent with these observations we demonstrated that, in general, CR in HFD-induced obese mice reduced body weight by~7 g and fat mass by 4e5 g within 20 days.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent time course studies show that this ghrelin resistance occurs after just 3 weeks exposure to HFD (Briggs et al, 2014)and that ghrelin resistance was reversible after diet-restricted weight loss (Briggs et al, 2013). In this study, we determined if HFD causes ghrelin resistance in the VTA, a key nodefor reward processing.…”
Section: Discussionmentioning
confidence: 95%
“…These deficits occur after several weeks of HFD feeding (Briggs et al, 2014), and persist while body weight remains high, but can be reversed with dietinduced weight loss (Briggs et al, 2013). Others have recently demonstrated ghrelin resistance in the vagal afferents and nodose ganglion, suggesting that this phenomenon is not limited to the hypothalamus (Naznin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Diet-induced obesity causes central ghrelin resistance (14), but enforced CR restores ghrelin sensitivity, which in turn promotes weight rebound (15). To see if long-term high BChE and low acyl-ghrelin levels affected ghrelin receptor sensitivity, we tested acyl-ghrelin's power to stimulate appetite and growth hormone release.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that ghrelin receptor sensitivity also responds to body weight. Thus, diet-induced weight gain causes central ghrelin resistance (14) while CR and body weight loss restore receptor sensitivity (15). Recently, Zigman et al (16) raised the idea that obesity-induced central ghrelin resistance can be reversed by dietinduced weight loss and that the restored receptor sensitivity may well be the major factor that drives rebound weight gain.…”
mentioning
confidence: 99%